An investigation of the impacts of intra-seasonal rainfall variability on the maize growing season in Limpopo Province, South Africa from 1990-2014 - Ramugondo, Ntanganedzeni (University of Cape Town, 2021)
Rain fed maize is an important staple food crop for rural communities in Southern Africa as it plays a major role in ensuring food security and improving livelihoods. Rainfall consistency and intensity is an essential requirement for successful maize growing seasons. The variability of intra-seasonal rainfall characteristics such as onset, cessation and wet and dry spells threatens maize yields in Southern Africa. Previous studies have focused on the impacts of seasonal rainfall totals on maize yields. The aim of this study is to investigate the impacts of intra-seasonal rainfall variability on the maize growing season of Limpopo Province, South Africa from 1990 to 2014. A Self-Organizing Map (SOM) is used to identify and distinguish synoptic states and patterns that are conducive for growing maize in the province from those that are not. The SOM is trained using daily mean Geopotential height reanalysis data, composites for rainfall and moisture are then analysed to understand surface responses. CHIRPS daily rainfall data is used to analyse the variability of rainfall characteristics. The relationship between these rainfall characteristics and maize yield is evaluated to assess the impacts of variability on maize yields. The SOM shows that summer maize growing season is characterised by low pressure systems over the mainland which act as tropical sources of moisture and the formation of cloud-bands associated with Tropical Temperate Troughs. There is a trend in late rainfall onset and earlier cessation leading to a shift and shortening of the rainy season. The shifted and shortened rainy seasons are characterised by dry spells and high intensity rainfall events and are potentially more suitable for planting the shorter season maize cultivars. Regardless of these agrometeorological conditions being detrimental to yields, district level and provincially averaged maize yields show an overall increasing trend. This is a result of improved farming methods such as planting drought resistant short season yellow maize cultivars which can withstand dry spells.